(untitled) (Academicia Globe: Inderscience Research, 2022)
This study is aimed at determining the foundations for constructing model characteristics of preparedness of taekwondo athletes. The effectiveness of managing the training process of taekwondo athletes is increased through the use of new model characteristics of the preparedness of athletes.